Japanese encephalitis - Rampengan, Novie H. (Jurnal Biomedik : JBM, 2016)
Abstract: Japanese encephalitis (JE) is an acute infective disease in the central nervous system. Pigs and birds are the main reservoirs of JE viruses, albeit, there is no transmission from human to human with mosquito bites. Clinical manifestations of JE in human vary from mild symptoms like rhinitis until severe symptoms, and even death. Incubation period of JE varies from 4 until 14 days. Development of JE symptoms are divided into 4 stadiums, as follows: prodormal, acute, sub-acute, and convalescent. Diagnosis is based on anamnesis about fever and the presence of pig farm around the house, and physical examination consisted of increased intra-cranial pressure and decreased consciousness, meanwhile, the definite diagnosis is confirmed with virus isolation either IgM capture ELISA test from serum or cerebrospinal fluid; both have sensitivity almost 100%. Treatment of JE is only symptomatic and supportive. Prevention and erradication of JE virus are aimed to human, mosquito Culex as vector and its larvae, and pig as the reservoir. Japanese encephalitis can be prevented with immunization. In severe cases, sequelae are found around 40%-75%.Keywords: Japanese encephalitis, culex mosquito, pig farm, vaccinationAbstrak: Japanese encephalitis (JE) merupakan penyakit infeksi akut pada SSP. Babi dan unggas merupakan reservoir virus ini, namun tidak terjadi penularan dari manusia ke manusia lain melalui gigitan nyamuk. Manifestasi klinis penyakit JE pada manusia bervariasi, mulai dari gejala ringan seperti demam flu biasa sampai berat bahkan kematian. Masa inkubasi JE bervariasi antara 4 sampai 14 hari. Perkembangan gejala JE terbagi atas 4 stadium yaitu stadium prodormal, akut, sub-akut, dan konvalesen. Diagnosis pasti dengan anamnesis adanya perternakan babi disekitar rumah dan demam, pemeriksaan fisik terdapat peningkatan tekanan intra kranial serta penurunan kesadaran, dan diagnosis pasti dengan isolasi virus maupun pemeriksaan IgM capture ELISA dari serum atau CSS dengan sensitivitas hampir 100%. Terapi JE hanya bersifat simtomatis dan suportif. Pencegahan dan pemberantasan JE virus ditujukan pada manusia, vektor nyamuk Culex beserta larvanya, dan reservoir babi. Penyakit JE dapat dicegah dengan imunisasi. Pada kasus berat, ditemukan gejala sisa sekitar 40%-75%.Kata kunci: Japanese encephalitis, nyamuk Culex, peternakan babi, imunisasi